Cox, Derek (London, 2006)
2006 "Cox, Derek", 2006, Bishopsgate Institute Derek Cox has been a youth and community worker for over 40 years and worked for Avenues Unlimited in Brick Lane. It employed the first full-time Asian youth worker, Ashok Basu Dev, in the early 1970s. Derek was involved in setting up the Montefiore Community Centre. He now works for New Avenues, the successor to Avenues Unlimited. Derek is still working as a full time youth and community worker.